Peroxidase-Catalyzed and Photo-Oxidation of Tryptophan Results in Distinct Isomeric Tryptophan Dimers - Morales, Marcela; Villegas, Daniel; Fierro, Angélica; Aranda, Mario; Carneiro, Maria Fernanda Hornos [UNESP]; Davies, Michael J.; López-Alarcón, Camilo (American Chemical Society (ACS), 2025)
Heme peroxidases, including horseradish peroxidase (HRP), catalyze the oxidation of a wide variety of substrates by hydrogen peroxide (H2O2) via the peroxidase cycle of these enzymes. Oxidation of free tryptophan (Trp) by HRP/H2O2 has been previously reported, but the formation of tryptophan dimers (di-Trp), which are biologically relevant, has not been studied. Here, we report on di-Trp production arising from oxidation of free Trp, at pH 5.5 and 9.2, by HRP/H2O2, as determined by liquid chromatography-mass spectrometry (LC-MS/MS) and selected reaction monitoring (SRM). These data were compared with those from riboflavin-sensitized photo-oxidation, and the products were rationalized by in silico studies. Incubation of varying concentrations of Trp and H2O2 with HRP, irrespective of the pH, resulted in the consumption of ∼2 mol of Trp per mole H2O2. Formation of multiple di-Trp isomers was detected, using m/z 407 → 203 and m/z 407 → 390 transitions, with greater yields detected at pH 9.2 than 5.5. These results contrast with riboflavin-mediated photo-oxidation where one di-Trp dimer predominated as detected by the m/z 407 → 203 transition. In silico docking studies suggest di-Trp formation within the catalytic pocket of HRP, and subsequent release is a probable mechanism, although other alternative scenarios are also possible.